Educating Your State Legislators - Stacey Ellison; Grace Carter (EDIS)
Both legislators and citizens play important roles in ensuring a fair and effective state government. Florida State Representatives and Senators have a responsibility to represent the will of their constituents. Similarly, citizens have a responsibility to educate their Representatives and Senators on how issues may impact them and other local citizens. This three-page guide walks you through the process of making your voice heard and provides some helpful tips to make your message to your legislator stand out. Written by Stacey Ellison and published by the UF/IFAS 4-H Youth Development Department, March 2019. http://edis.ifas.ufl.edu/4h397